Estimation of lung volume in infants by echo planar imaging and total body plethysmography. Issue 2 (February 1990) - Chapman, B; O'Callaghan, C; Coxon, R; Glover, P; Jaroszkiewicz, G; Howseman, A; Mansfield, P; Small, P; Milner, A D; Coupland, R E
Abstract : Echo planar imaging (an extremely fast method of magnetic resonance imaging) was used to measure lung volume in a group of nine infants, all of whom had had respiratory problems. The mean echo planar imaging estimate of total lung volume was 44 +/- 9 ml/kg. In each case the right lung was larger than the left (ratio 52.8:47.2%). The mean thoracic gas volume was 36 +/- 8 ml/kg. The entire sequence of images of the thorax (about 400) takes five minutes to complete, infants require no sedation, and there are no side effects.